2006
DOI: 10.1007/s10811-006-9025-y
|View full text |Cite
|
Sign up to set email alerts
|

Farming of the Giant Kelp Macrocystis Pyrifera in Southern Chile for Development of Novel Food Products

Abstract: This study explores the potential cultivation of the giant kelp Macrocystis pyrifera (L.) C.A. Agardh in southern Chile, for the development of novel food products. The study demonstrates the importance of considering the collection site of the parent sporophytes for successful cultivation. This study also shows that the ropes must be seeded with 10,000 to 40,000 spores ml −1 , depending on the culture method used. We also demonstrated that under environmental conditions in southern Chile, the seeded ropes mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 13 publications
2
22
1
Order By: Relevance
“…The identification of higher value products and extracts from macroalgae will serve as an added argument in support of their production in IMTA systems. For instance, Macrocystis, a low-value genus harvested for its alginates, has recently been used in higher valued edible products, and as organic feed for abalone (Gutiérrez et al, 2006;Flores-Aguilar et al, 2007). The utilization of seaweeds for aquafeeds is an emergent research priority for the aquaculture industry, and this may act as an additional convincing point to the industry to deploy IMTA systems.…”
Section: Internal Economic Considerationsmentioning
confidence: 99%
“…The identification of higher value products and extracts from macroalgae will serve as an added argument in support of their production in IMTA systems. For instance, Macrocystis, a low-value genus harvested for its alginates, has recently been used in higher valued edible products, and as organic feed for abalone (Gutiérrez et al, 2006;Flores-Aguilar et al, 2007). The utilization of seaweeds for aquafeeds is an emergent research priority for the aquaculture industry, and this may act as an additional convincing point to the industry to deploy IMTA systems.…”
Section: Internal Economic Considerationsmentioning
confidence: 99%
“…To provide the suspended culture centres with young sporophytes, two different methodologies were developed: free-floating sporophytes (following Westermeier et al 2006 protocol) and rope-seeded sporophytes (following Gutierrez et al 2006 protocol and optimized following Camus & Buschmann 2017) ( Fig. 2).…”
Section: Experimental Seedling Productionmentioning
confidence: 99%
“…One of the most exploited resources is the giant kelp Macrocystis pyrifera (Linnaeus) C. Agardh or 'huiro', which inhabits the Chilean coast from Arica to the Magallanes region, covering more than 4000 kilometres of coast (Hoffmann & Santelices 1997). The principal markets are as fresh biomass for abalone feed (Correa et al 2016), as dry biomass for alginate extraction (Indergaard & Østgaard 1991), as potential food (Gutierrez et al 2006) and as biomass to produce plant growth enhancers (Buschmann et al 2008). Recently, new possible markets are under development for M. pyrifera, like human consumption (mini-seavegetables, www.elrepuertero.cl) and biofuel/chemical production (Song et al 2015;Suutari et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general agreement on the importance of the holdfast as a taxonomic feature was questioned when Hay (1986) described a fourth species, M. laevis C. H. Hay, present at Marion Island (SW Indian Ocean), primarily based on the morphology of its smooth blades and vesiculate sporophylls; however, it possessed a conical holdfast similar to M. pyrifera. Aguilar-Rosas et al (2003) also collected M. laevis in southern Chile, but this record has been questioned (Gutierrez et al 2006). North (1994) observed that if using blade features finds general acceptance by algal taxonomists, possibilities exist for the creation of additional species within the genus due to the high plasticity in blade and holdfast morphologies.…”
mentioning
confidence: 99%